Respiratory support strategy in 499 preterm newborns with gestational age ≤ 32 weeks - Sara Aguilar; Teresa Rodrigues; Margarida Albuquerque; Isabel Sampaio; Bruno Cardoso; Leonor Boto; Carlos Moniz; Graça Oliveira (Hygeia Press di Corridori Marinella, 2013)
Objectives: To evaluate the respiratory support strategy and its association with morbidity and mortality in preterm infants with Gestational Age (GA) ≤ 32 weeks, admitted between 2000 and 2008. Methods: Chart data from newborns with GA ≤ 32 weeks admitted to a tertiary Neonatal Intensive Care Unit between 2000-2008, were reviewed retrospectively. Newborns were divided into two groups according to the year of birth: Group 1 (2000-2004) and Group 2 (2005-2008). Each group of newborns was subdivided in subgroups according to their GA: 23-28 gestational weeks and 29-32 gestational weeks. Each group was compared in terms of ventilation and surfactant strategy, morbility and mortality. The statistical analysis was carried out with SPSS 21.0. Results: We included 499 newborns, 224 in Group 1 and 275 in Group 2. The mean GA, sex and birth weight were similar in both groups. The comparison of the two groups showed a statistically significant difference in the rate of invasive ventilation and surfactant strategy. The mortality before discharge rate was 17.4% for Group 1 and 13.5% for Group 2. The comparison of the subgroups, revealed a statistically higher incidence of INSURE strategy and noninvasive ventilation in newborns born after 2004, with reduction of the mortality rate in newborns with GA comprised between 29-32 weeks and reduction of pneumothorax, severe chronic lung disease and intraventricular hemorrhage in newborns with GA comprised between 23-28 weeks. Conclusion: There was a tendency towards non-invasive strategy and INSURE administration of surfactant over the years. Mortality and major morbidity decreased along with these changes in the therapeutic approach of the respiratory distress syndrome in preterm newborns.